2019
DOI: 10.1186/s41240-019-0135-2
|View full text |Cite
|
Sign up to set email alerts
|

Study of pathogenicity and severity of Lactococcus garvieae isolated from rainbow trout (Oncorhynchus mykiss) farms in Kohkilooieh and Boyerahmad province

Abstract: Background: Lactococcus garvieae is one of the most important risk factors in the rainbow trout culture. Therefore, the purpose of this study was to identify and detect strains isolated from rainbow trout suspected of having Lactococcus garvieae using biochemical characteristics and PCR and determination of the degree of severity of isolated strains. Methods: In this study, the cause of lactococcosis in selected rainbow trout farms in Kohkilooieh and Boyerahmad province was assayed. Gram-positive and catalase-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
3
8
0
Order By: Relevance
“…The highly virulent nature of a Californian trout L. garvieae isolate was confirmed in laboratory-controlled challenges, which determined an LD 50 of ∼20 CFU/mL 21 dpc. Results were similar to the 1.25 × 10 1 CFU/mL reported by Eldar and Gittino (1999), but lower than LD 50 values of 10 2 CFU/mL (Pereira et al, 2004), 7.4 × 10 5 CFU/mL (Karami et al, 2019), 6 × 10 5 CFU/mL (Sharifiyazdi et al, 2010) and 1.7 × 10 5 CFU/mL (Türe et al, 2014) determined for other trout isolates using the same infection route. The differences could be the result of bacterial strain virulence, fish susceptibility (e.g.…”
Section: In Vivo Challengessupporting
confidence: 90%
See 1 more Smart Citation
“…The highly virulent nature of a Californian trout L. garvieae isolate was confirmed in laboratory-controlled challenges, which determined an LD 50 of ∼20 CFU/mL 21 dpc. Results were similar to the 1.25 × 10 1 CFU/mL reported by Eldar and Gittino (1999), but lower than LD 50 values of 10 2 CFU/mL (Pereira et al, 2004), 7.4 × 10 5 CFU/mL (Karami et al, 2019), 6 × 10 5 CFU/mL (Sharifiyazdi et al, 2010) and 1.7 × 10 5 CFU/mL (Türe et al, 2014) determined for other trout isolates using the same infection route. The differences could be the result of bacterial strain virulence, fish susceptibility (e.g.…”
Section: In Vivo Challengessupporting
confidence: 90%
“…garvieae from Iran, Turkey and Japan likewise show variable sensitivities to antimicrobial agents (Balta & Balta, 2019;Karami et al, 2019;Maki et al, 2008;Sharifiyazdi et al, 2010;Soltani et al, 2008).…”
Section: In Vivo Challengesmentioning
confidence: 99%
“…The development of a disease depends primarily on the virulence of the bacteria, the characteristics of the host infected, the route of infection, the age of the fish infected, the quality of water, and other environmental factors (Meyburgh et al., 2017; Sudheesh et al., 2012). The pathogenic mechanism underlying L. garvieae infection involves the formation of vascular endothelial lesions that lead to the manifestation of petechiae and disseminated inflammation in fish (Meyburgh et al., 2017), where the severity of infection or symptoms can vary depending on the host organism (Karami et al., 2019). The gross histopathological observation in the present case study were consistent with previous findings of anaemia, pale gills, renomegaly, splenomegaly, congestion and haemorrhages in heart, liver, kidney, spleen and brain, leading to partial degeneration (Chang et al., 2002; Chen et al., 2002; Meyburgh et al., 2017; Shahi et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the pathogenicity of Chryseobacterium in farmed fish is comparably lower than the major bacterial pathogens (e.g., Flavobacterium and Lactococcus) and earlier studies reported 5 LogCFU/fish as the median lethal dose of Chryseobacterium [33,34]. The LD50 of C. cucumeris in pond loach was 7.8 LogCFU/fish [32], whereas the LD50 of C. indologenes in yellow perch was 8.1 LogCFU/fish [35].…”
Section: Discussionmentioning
confidence: 90%
“…The C. scophthalmum TPBLGL 18 infection in golden mahseer resulted in median lethal dose of 6.2 LogCFU/fish [36]. Although the pathogenicity of the Chryseobacterium was not much greater than the common pathogens, multidrug-resistant features of the strain WLT may pose a therapeutic challenge [33,34]. Therefore, Chryseobacterium could be considered as a fish pathogenic microoganism in addition to its food spoilage activity.…”
Section: Discussionmentioning
confidence: 99%